A new approach for the microencapsulation of curcumin by a spray drying method, in order to value food products - Lucas, J (2020)
Curcumin has been incorporated for the development of new products with applicability in food, pharmaceutical and cosmetic fields. However, the poor solubility in aqueous systems and very high sensitivity are the main concerns that need to be overcome during storage and processing. Microencapsulation technology may provide the required protection and stabilization of curcumin, preventing or reducing its degradation. The present work focuses on a new approach for the microencapsulation of curcumin from turmeric oleoresin (in alcoholic solutions) by a spray drying process using different biopolymers such as gum arabic, sodium alginate and a water-soluble modified chitosan as wall materials. Thus, a series of curcumin microcapsules were prepared and their physicochemical properties were analysed by laser granulometry and by scanning electron microscopy (SEM). Spherical microparticles with a mean diameter between 9 and 30 mu m, considering a volume distribution, have been observed for all the biopolymers tested. The microparticles formed with gum arabic and alginate presented a very rough surface; on the other hand, the particles formed with the modified chitosan presented a smooth surface. The product yield obtained for the microparticles ranged from 46.1% to 57.3%. Curcumin release studies were performed and validated by a UV/VIS spectrophotometer using absorbance analysis. The results showed that all release profiles were similar, however with different total release times: 35 min, 2 h and 4 h for modified chitosan, alginate and gum arabic respectively, and the encapsulation efficiencies (EE) are between 93.8% and 97.6%. Moreover, all curves fit well to the Weibull model and to the Korsmeyer-Peppas model. This work shows that it is possible to encapsulate curcumin (in alcoholic solutions) using different biopolymers, through a spray-drying process.